Vertrauen im Konflikt: Eine Grundlegung - Rainer Forst (Normative Konstituenzien der Demokratie, 2024)
– This paper challenges widespread assumptions in trust research according to which trust and conflict are opposing terms or where trust is generally seen as a value. Rather, it argues that trust is only valuable if properly justified, and it places such justifications in contexts of social and political conflict. For these purposes, the paper suggests a distinction between a general concept and various conceptions of trust, and it defines the concept of a trust relation as a four-place one. With regard to the justification of trust, a distinction between internal and full justification is introduced, and the justification of trust is linked to relations of justification between trusters and trusted. Finally, trust in conflict(s) emerges where such relations exist among the parties of a conflict, often by way of institutional mediation.
Keywords: 300